Empowering community voices in land use planning and decision-making using PPGIS - A case study from the Westfjords, Iceland - Ólafsdóttir, Rannveig; Bishop, Michaël; Edvardsdóttir, Anna Guðrún; Welling, Johannes; Tuulentie, Seija (Taylor & Francis, 2026)
This paper explores how public participation in land-use planning contributes to community well-being and evaluates the effectiveness of PPGIS combined with focus group discussions for assessing residents’ land-use preferences and concerns. An online PPGIS survey was conducted in a rural community in the Westfjords of Iceland, followed by on-site focus groups to obtain a deeper understanding of residents’ attitudes towards aquaculture and tourism and their associated economic, social, and environmental impacts. The results reveal a strong willingness among residents to be actively involved in land-use planning and decision-making. While aquaculture and tourism are perceived as important economic opportunities, they are also seen as insufficient to sustain the community’s social and environmental structure. This emphasizes the need to integrate socio-ecological considerations into land-use planning, and highlights the importance of inclusive, collaborative decision-making approaches that prioritize community well-being and environmental stewardship amid the Arctic’s rapid environmental and economic changes.
Keywords: tourism; aquaculture; Land-use conflicts; rural development; public participation; community well-being